FACTORS INFLUENCING ADOPTION OF RECOMMENDED RICE PRODUCTION PRACTICES IN TWO SELECTED LOCAL GOVERNMENT AREAS OF KOGI STATE, NIGERIA - Alabi*, S.I.; Saddiq, N.M.; Abudu, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study analysed the factors influencing adoption of recommended rice production practices in two selected L.G.As of Kogi State, Nigeria. A Multistage sampling procedure was used to select 201 respondents. The study relied mainly on primary data which was achieved via a structured questionnaire. Descriptive statistics and inferential statistic were employed to achieve the stated objectives. Results on the socioeconomic and institutional characteristics revealed that, the rice farmers were in their active age with the mean age of 43 years and majority (87.6%) were married. In addition, results on factors influencing the adoption of recommended rice production practices by farmers shows that, sex (p≤0.10), farm size (p≤0.05), farming experience (p≤0.10), and number of visit (p≤0.10) influence the adoption of recommended rice production practices. Furthermore, high cost of agro-chemicals (99%), scarcity of farm machinery (98%) and high cost of inputs (97.5%) were the major constraints faced by rice farmers in the study area. It was recommended that NCRI should endeavour to train rice farmers on how to turn house and farm waste product into manure to augment the use of agrochemical. Also, Rice farmers’ cooperatives, government agencies and private enterprises through public-private partnership (PPP) should establish farm machineries leasing services to curtail the constraint on scarcity of machineries.